68Ga-Exendin-4 PET/CT in Evaluation of Endoscopic Ultrasound–Guided Ethanol Ablation of an Insulinoma. (April 2017) - Luo, Yaping; Li, Ji; Yang, Aiming; Yang, Hongbo; Li, Fang
Abstract : Abstract: A 32-year-old man with endogenous hyperinsulinemic hypoglycemia was clinically diagnosed with an insulinoma. Conventional imaging result was negative, and a previous exploratory laparotomy with distal pancreatectomy failed to detect the tumor. 68 Ga-exendin-4 PET/CT showed a lesion with intense radioactivity in the head of the pancreas suggestive of an insulinoma, and endoscopic ultrasound-guided ethanol ablation was performed. Postablation evaluation with 68 Ga-exendin-4 PET/CT showed markedly decreased radioactivity of the tumor. The symptoms and blood glucose monitoring also suggested partial response of the insulinoma.